KONSTRUKSI KAFIR DALAM DISKURSUS TASAWUF: ANALISIS WACANA KRITIS KATA KAFIR PADA KITAB HÂDZÂ AL-KITÂB MATN AL-HIKAM KARYA KIAI SHOLEH DARAT - Ahmad Umam Aufi; Muslich Shabir (UIN Antasari Banjarmasin, 2022)
This paper aims to look at the construction of the word kafir in Sufism discourse using Norman Fairclough's critical discourse analysis approach. This paper examines the term kafir in the holy book Hâdzâ al-Kitâb Matn al-Hikam li Sayyidī Syaikh Ahmad ibn 'Athâillâh al-Sakandârî by kiai Sholeh Darat. The results of this discussion show that the word kafir in Sufism is not synonymous with non-Muslim but refers to tadbîr, lacut (beyond the limit) when feeling rich, and not grateful for God’s mercy. The construction of the word infidel is influenced by the Sunni Sufism style adopted by Kyai Sholeh Darat. The construction of the term kafir is also in order to maintain monotheism and optimism of Muslims during the difficult times experienced in the 19th century. This happened because of the impact of the policy of the forced cultivation system, the domination of the colonial government in all aspects of people's lives and the strengthening of the unequal economic structure and the structure of Javanese foedalism. The impact of the construction of kiai Sholeh Darat on the term kafir is not to worry about any worldly affairs such as sustenance and directing Muslim life to concentration on the path of worship such as science and spiritual activities which later gave birth to the strength of the pesantren and tarekat network in resisting colonialism.Tulisan ini bertujuan untuk melihat konstruksi kata kafir dalam diskursus tasawuf dengan menggunakan pendekatan analisis wacana kritis Norman Fairclough. Tulisan ini mengkaji kata kafir dalam kitab Hâdzâ al-Kitâb Matn al-Hikam li Sayyidī Syaikh Ahmad ibn 'Athâillâh al-Sakandârî karya kiai Sholeh Darat. Hasil dari pembahasan ini menunjukkan bahwa kata kafir dalam tasawuf tidak identik dengan non muslim melainkan merujuk pada tadbîr, lacut (melampaui batas) saat merasa kaya, dan tidak mensyukuri nikmat. Konstruksi kata kafir ini dipengaruhi corak tasawuf sunni yang dianut kiai Sholeh Darat. Konstruksi kata kafir juga dalam rangka memelihara ketauhidan dan optimisme umat Islam pada masa-masa sulit yang dialami di abad ke-19. Hal tersebut terjadi karena dampak kebijakan sistem tanam paksa, dominasi pemerintah kolonial pada seluruh aspek kehidupan masyarakat dan menguatnya struktur ekonomi yang timpang dan struktur foedalisme Jawa. Dampak dari konstruksi kiai Sholeh Darat atas term kafir yaitu tidak mengkhawatirkan setiap urusan duniawi seperti rezeki dan mengarahkan kehidupan muslim pada konsentrasi di jalur ibadah seperti ilmu pengetahuan dan aktivitas ruhani yang kelak melahirkan kekuatan jaringan pesantren dan tarekat dalam melawan kolonialisme.